Penerapan Pendidikan Karakter di Era Digital Melalui Kegiatan Bazar Bulanan (Monthly Bazaar) - Zakiyah Ismuwardani; Sri Hastuti (Publikasi Pendidikan, 2021)
This study aims to make students have an independent character, discipline and responsibility in the digital era through the Monthly Bazaar. The method used in this research was Mixed Method with a sequential exploratory strategy. The sequential exploratory strategy involves collecting and analyzing quantitative data in the second stage based on the results of the first stage. Weights / priorities are more likely to be in the first stage, and the mixing process between these two methods occurs when the researcher makes a connection between qualitative data analysis and quantitative data collection. The results of the study were obtained from qualitative data analysis in the first stage and quantitative data in the second stage. The results of the first stage were obtained from educators' observations of students after completing the monthly bazaar. The results of the second stage are obtained through calculations using a Likert scale and it is obtained the data of 43.75% (ever) if it is categorized in interpretation of scores based on intervals. This data was obtained before the implementation of the monthly bazaar. After implementing the monthly bazaar for two times, the data is 72.75% (often). From the two stages, the relevant results obtained between qualitative and quantitative data analysis showed that there was an independent character, discipline and responsibility embedded in students after the implementation of the monthly bazaar activities.